High-dose lipopolysaccharide induced autophagic cell death in bovine mammary alveolar cells - Jin-Ki Park; Joon Mo Yeo; Kwanghyun Cho; Hyun-Jung Park; Won-Young Lee (The Korean Society of Animal Reproduction and Biotechnology, 2022)
Bovine mammary epithelial (MAC-T) cells are commonly used to study mammary gland development and mastitis. Lipopolysaccharide is a major bacterial cell membrane component that can induce inflammation. Autophagy is an important regulatory mechanism participating in the elimination of invading pathogens. In this study, we evaluated the mechanism underlying bacterial mastitis and mammary cell death following lipopolysaccharide treatment. After 24 h of 50 μg/mL lipopolysaccharide treatment, a significant decrease in the proliferation rate of MAC-T cells was observed. However, no changes were observed upon treatment of MAC-T cells with 10 μg/mL of lipopolysaccharide for up to 48 h. Thus, upon lipopolysaccharide treatment, MAC-T cells exhibit dose-dependent effects of growth inhibition at 10 μg/mL and death at 50 μg/mL. Treatment of MAC-T cells with 50 μg/mL lipopolysaccharide also induced the expression of autophagy-related genes ATG3, ATG5, ATG10, ATG12, MAP1LC3B, GABARAP-L2, and BECN1. The autophagy-related LC3A/B protein was also expressed in a dose-dependent manner upon lipopolysaccharide treatment. Based on these results, we suggest that a high dose of bacterial infection induces mammary epithelial cell death related to autophagy signals.